Inoculation and habitat amelioration efforts in biological soil crust recovery vary by desert and soil texture. (8th January 2020) - Faist, Akasha M.; Antoninka, Anita J.; Belnap, Jayne; Bowker, Matthew A.; Duniway, Michael C.; Garcia‐Pichel, Ferran; Nelson, Corey; Reed, Sasha C.; Giraldo‐Silva, Ana; Velasco‐Ayuso, Sergio; Barger, Nichole N.
Abstract : As dryland degradation continues, it is increasingly important to understand how to effectively restore biocrust communities. Potential techniques include the addition of biocrust inoculum to accelerate biocrust recovery. Enhanced erosion typical of degraded environments creates a challenge for these approaches, due to loss by wind or water and burial by saltating particles. To retain and protect added inoculum, the inclusion of habitat‐amelioration techniques can improve recovery rates. This study tested three different types of inoculum (field‐collected, greenhouse‐cultivated, and laboratory‐cultivated biocrust) coupled with two treatments to augment soil stability and ameliorate habitat limitations: soil surface polyacrylamide additions and installation of straw barriers. This was done across two deserts (Great Basin and Chihuahuan) and separated into generally coarse‐ or finer‐textured soils in each desert, with results monitored for 3 years (2015, 2016, 2017). While the inoculum type, coupled with habitat ameliorations, occasionally enhanced biocrust growth across years and treatments, in other cases, it made no difference compared to natural recovery rates. Rather, the desert location and soil texture groupings were the most prominent factors in determining recovery trajectories. Recovery proportions were similar in the finer‐textured sites in both the Great Basin and the Chihuahuan deserts, while the coarser‐textured site in the Great Basin did show some recovery over time and the Chihuahuan coarser‐textured site did not. This study demonstrates the importance of understanding site potential and identifying key limitations to biocrust recovery for successful restoration projects.